Mannitol Cream for Pain Control, a Chart Review - Helene Bertrand (Taylor & Francis Group, 2019)
Introduction/Aim: topical mannitol was shown to down regulate the capsaicin pain receptor. How effective would it be for pain control in clinical practice? Methods: a chart review of 235 patients who received a 30% mannitol, cream for pain. Each patient used the cream on whatever part of their body was painful. Their chart contained a data sheet with: date, time, numeric pain score 0 = no pain to 10 = worst imaginable pain before and 30 minutes after application, minutes until relief, duration of relief. Results: Of the 235 participants, there were 366 different areas of the body that were treated. The average pain relief was 50.8% (SD 29.8), median 52.94%. Areas of the body experiencing over 60% relief were the thumb and fingers, wrists, thigh, leg and knee (where the affected nerves are closest to the skin surface). The following areas had pain relief scores between 50% and 59%: foot, neck, arm, hip and back. 7 people developed a transient rash in the area where the cream was being applied, which resolved when cream use was stopped. Discussion/Conclusions: The average pain relief for mannitol cream was 50.8% whereas for narcotics it is 36%, for oral or topical NSAIDS it is 23% and acetaminophen it is 13%. This is, however, only a retrospective observational study, not a randomized placebo-controlled study so it is, subject to the placebo effect. Topical mannitol may prove useful in providing pain relief. It needs to be tested in a randomized, placebo-controlled study which is currently underway.